Assessing the Alignment Between Graduate Competencies and Workplace Needs: Evidence from Indonesian Language Education Graduates at State Islamic University of North Sumatera - Indra Rasyid Julianto; Anugerah Agung Pohan (Jurnal Pendidikan Edutama, 2026)
The alignment between graduate competencies and workplace needs is a key indicator of higher education quality. This study aims to examine the relevance of the competencies of graduates from the Indonesian Language Education Study Program at State Islamic University of North Sumatera (UINSU) from the perspectives of alumni and employers. A descriptive qualitative approach was employed, supported by quantitative data obtained from tracer studies and employer satisfaction surveys. The participants consisted of alumni and five employers from educational institutions that employ program graduates. Data were collected through questionnaires, in-depth interviews, and document analysis. The findings indicate that graduate competencies are generally aligned with workplace demands. This is reflected in a graduate employment rate of 86.6%, with 93.3% of alumni working in the education sector. Employer satisfaction was particularly high regarding graduates’ ethical behavior (76.7% rated very good), educational expertise (70%), communication skills (66.7%), self-development abilities (66.7%), information technology skills (63.3%), and teamwork capabilities (63.3%). Interview results further revealed that graduates possess strong pedagogical, professional, social, and personal competencies. However, improvements are still needed in foreign language proficiency, instructional innovation, the use of digital learning technologies, and the development of technology-based learning media. The study recommends strengthening the Outcome-Based Education (OBE) curriculum, expanding field practice opportunities, and integrating twenty-first-century skills into the learning process to enhance graduate competitiveness and professional readiness.